1993
DOI: 10.2166/wst.1993.0223
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of Constructed Wetlands for Wastewater Treatment in Northern Environments

Abstract: Constructed wetlands consist of soil filled beds with aquatic plants. Wastewater is treated when flowing through these beds. It has been questioned if constructed wetlands will be able to operate when subjected to cold conditions in sub arctic regions. Experience from Norway indicates that significant biological activity occurs at temperatures between 0 and 5°C, and that high removal rates of nutrients and organic matter are achieved in ponds and soil amended with wastewater at these temperatures. Results from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
57
0
3

Year Published

2000
2000
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(60 citation statements)
references
References 0 publications
0
57
0
3
Order By: Relevance
“…As one of the main biological components of freshwater systems, aquatic plants or macrophytes not only assimilate pollutants directly into their tissues, but can also act as catalysts for purification reactions by increasing environmental diversity in the rhizosphere, thereby promoting various chemical and biochemical reactions that enhance purification [10]. These plants are also important since they are a source of oxygen, provide food, shade and cover for fish and other aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the main biological components of freshwater systems, aquatic plants or macrophytes not only assimilate pollutants directly into their tissues, but can also act as catalysts for purification reactions by increasing environmental diversity in the rhizosphere, thereby promoting various chemical and biochemical reactions that enhance purification [10]. These plants are also important since they are a source of oxygen, provide food, shade and cover for fish and other aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Brix (1990) found that the ability of macrophytes to provide oxygen was limiting nitrification in horizontal subsurface flow CWs. In Norway, where plants are dormant during the cold season this has been overcome by using an aerobic biofilter (pre-treatment filter) preceding the horizontal subsurface flow wetland filter (Jenssen et al, 1993). The use of LWA with well-defined properties has simplified design of these treatment systems (Maehlum and Jenssen, 2002;Jenssen and Krogstad, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…It was expected that the experimental pots containing coconut flake with and without planting Pudsaon used water through evapotranspiration process could make room temperature decreasing (Juwarkar et al, 1995;Hammer, 1989;Ahn & Mitsch, 2002;Jenssen et al, 1994;Keddy, 2010;Bowen, 1926;Lai et al, 2011;Dicken et al, 2013;Gates, 1980;Hartman, 1994;Holland et al, 2013;Coseo & Larsen, 2014).…”
Section: Useable Pudsaon For Sensible Heat Absorptionmentioning
confidence: 99%